Countries of the world and their leaders yearbook 2013 - Ellicott, Karen (Gale, 2012)
A compilation of U.S. Department of State reports on contemporary political and economic conditions, government personnel and policies, political parties, religions, history, education, press, radio and TV, climate, and other characteristics of selected countries of the world; together with travel alerts, passport and visa information, world health information for travelers, and customs and duty tips for returning residents.